2012
DOI: 10.1128/jvi.00286-12
|View full text |Cite
|
Sign up to set email alerts
|

Vicriviroc Resistance Decay and Relative Replicative Fitness in HIV-1 Clinical Isolates under Sequential Drug Selection Pressures

Abstract: We previously described an HIV-1-infected individual who developed resistance to vicriviroc (VCV), an investigational CCR5 antagonist, during 28 weeks of therapy (Tsibris AM et al., J. Virol. 82: 8210–8214, 2008). To investigate the decay of VCV resistance mutations, a standard clonal analysis of full-length env (gp160) was performed on plasma HIV-1 samples obtained at week 28 (the time of VCV discontinuation) and at three subsequent time points (weeks 30, 42, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Florescence changes were monitored over time using a 409 nm excitation and both a 460 nm (blue) and 528 nm (green) emission detection. We measured fusion for 100 minutes to capture maximum fusion, which was comparable to time points reported by others using similar assays [ 56 , 58 ]. We also noticed that control pseudoviruses without Env produced a time-dependent increase in background signal as incubation periods approach 100 min (Additional file 1 : Figure S1).…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…Florescence changes were monitored over time using a 409 nm excitation and both a 460 nm (blue) and 528 nm (green) emission detection. We measured fusion for 100 minutes to capture maximum fusion, which was comparable to time points reported by others using similar assays [ 56 , 58 ]. We also noticed that control pseudoviruses without Env produced a time-dependent increase in background signal as incubation periods approach 100 min (Additional file 1 : Figure S1).…”
Section: Methodsmentioning
confidence: 58%
“…We next assessed whether increased 6HB stability affected the rate of virus entry, since entry kinetics has been linked to susceptibility to inhibition by peptide fusion inhibitors [ 50 - 52 ]. To measure entry kinetics, we recorded fusion in real time using pseudoviruses that incorporated β-lactamase-Vpr enzyme, which cleaves a fluorescent substrate in the cytoplasm of target cells after virus entry [ 55 - 58 ]. This assay showed that five of six Envs selected in the resistance cultures conferred significantly slower (C1-C1, C2-C2, C6-C6, C4-C4, C5-C5) entry kinetics relative to WT (Figure 3 A-B; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Deep sequencing of VCV-treated patients showed rapid expansion of V3 sequence diversity and minor variants during treatment, indicating that variants that are initially less than 1% of the quasispecies can be clinically relevant [198]. Furthermore, co-evolution between gp120 and gp41 may help to maximize fitness and entry kinetics [199]. The quasispecies, therefore, provides a ready source of variants for sampling and finding an efficient pathway for resistance.…”
Section: Inhibitors Of Chemokine Receptor Interactionsmentioning
confidence: 99%
“…6) and changes in entry efficiency. [7][8][9][10][11] Selective pressure on Env derives primarily from the humoral immune response. Neutralizing antibodies are those that can prevent virus infection of a target cell.…”
Section: Introductionmentioning
confidence: 99%